Las noticias impresas en la Monarquía Hispánica (siglos XVI-XVIII): nuevos estudios y métodos - Firbas, Paul (2021)
This work presents the edited conversation of the symposium “Efímero: Early Modern News-Sheets and Pamphlets in the Hispanic World,” held virtually at Stony Brook University in March 2021 with specialists from Europe and the Americas. The text presents new research, methods, bibliography, and projects on sixteenth to eighteenth century printed news, with focus on the transatlantic circulation between Spain and Peru. Specifically, it discusses news networks, the editorial market in Lima (1700-1711), engravings and theater pamphlets related to relaciones de sucesos, censorship, and the circulation of ephemera.